Neutralising anti‐drug antibodies in Fabry disease can inhibit endothelial enzyme uptake and activity. Issue 2 (14th November 2019) - Stappers, Franciska; Scharnetzki, David; Schmitz, Boris; Manikowski, Dominique; Brand, Stefan‐Martin; Grobe, Kay; Lenders, Malte; Brand, Eva
Abstract: Fabry disease (FD) is a lysosomal storage disease, treatable by enzyme replacement therapy (ERT) that substitutes deficient α‐galactosidase A (AGAL). The formation of neutralising anti‐drug antibodies (ADA) inhibiting AGAL activity during infusion is associated with disease progression in affected male patients. In this study we analysed if ADAs also inhibit endothelial enzyme uptake as well as intracellular enzyme activity. Therefore, fluorescence‐labelled AGAL in combination with ADA‐positive sera from FD patients (n = 8) was used to analyse enzyme uptake in endothelial and FD‐specific cells. Furthermore, immune adsorption and a comprehensive ADA epitope mapping were performed. Pre‐incubation of AGAL with ADAs significantly inhibited intracellular enzyme activity, which was rescued by immune adsorption (both P  < .01). ADAs from some patients also inhibited enzyme uptake. ADA epitope mapping identified an epitope at position 121 to 140 aa potentially responsible for uptake inhibition for these patients. Further analyses revealed the presence of stable AGAL/ADA‐immune complexes at pH 4.5 and decreased intracellular enzyme activity in endothelial cells ( P  < .001). Finally, the pre‐incubation of AGAL with ADAs resulted in a reduced depletion of intracellular globotriaosylceramide in patient‐derived AGAL‐deficient cells, demonstrating a direct negative impact of ADAs on intracellular clearance. Neutralising ADAs may not only inhibit infused AGAL activity, but according to their epitopes can also inhibit endothelial AGAL uptake. Indeed, internalised AGAL/ADA‐complexes may not dissociate, underlining the importance of novel therapeutic approaches for ADA reduction and prevention to increase therapy efficiency in affected patients.